2004
DOI: 10.1091/mbc.e03-10-0744
|View full text |Cite
|
Sign up to set email alerts
|

Adaptor Protein Complex 1 Mediates the Transport of Lysosomal Proteins from a Golgi-like Organelle to Peripheral Vacuoles in the Primitive EukaryoteGiardia lamblia

Abstract: Giardia lamblia is an early branching protist that possesses peripheral vacuoles (PVs) with characteristics of lysosome-like organelles, located underneath the plasma membrane. In more evolved cells, lysosomal protein trafficking is achieved by cargo recognition involving adaptor protein (AP) complexes that recognize specific amino acid sequences (tyrosine and/or dileucine motifs) within the cytoplasmic tail of membrane proteins. Previously, we reported that Giardia has a tyrosine-based sorting system, which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(109 citation statements)
references
References 48 publications
(50 reference statements)
6
100
1
2
Order By: Relevance
“…To test whether the bioinformatic data correctly predict the compartment or pathway of a given SNARE, the 17 coding genes for putative gSNAREs were amplified by PCR from G. lamblia genomic DNA, cloned into an HA fusion vector, and transfected into G. lamblia trophozoites (37). It was shown previously that small tags such as the HA epitope do not influence the behavior of Giardia proteins and do not affect their subcellular localization (4,20). The HA epitope was inserted at the N terminus of these constructs because SNARE proteins do not have an N-terminal signal peptide (31) and also because it has been shown that this procedure accurately reflects the localization of SNARE proteins in other eukaryotic cells (54).…”
Section: Subcellular Distribution Of Gsnare Proteins In G Lambliamentioning
confidence: 99%
“…To test whether the bioinformatic data correctly predict the compartment or pathway of a given SNARE, the 17 coding genes for putative gSNAREs were amplified by PCR from G. lamblia genomic DNA, cloned into an HA fusion vector, and transfected into G. lamblia trophozoites (37). It was shown previously that small tags such as the HA epitope do not influence the behavior of Giardia proteins and do not affect their subcellular localization (4,20). The HA epitope was inserted at the N terminus of these constructs because SNARE proteins do not have an N-terminal signal peptide (31) and also because it has been shown that this procedure accurately reflects the localization of SNARE proteins in other eukaryotic cells (54).…”
Section: Subcellular Distribution Of Gsnare Proteins In G Lambliamentioning
confidence: 99%
“…Several groups have presented evidence for a role of clathrin in endocytosis in Giardia (Touz et al, 2004;Hernandez et al, 2007;Gaechter et al, 2008;Rivero et al, 2010). However, neither typical membrane-associated clathrin lattices nor emerging clathrin-coated pits have been observed in this parasite.…”
Section: Clathrinmentioning
confidence: 92%
“…In mammalian cells, it has been shown that TCs contain mannose-phosphate receptors, clathrin, Golgi-localizing Gamma-ear containing ARF-binding proteins (GGAs), and/or adaptor protein 1 (AP-1), and it was suggested that these might be uncoated during the TC-endosome fusion or could become integrated into the endosome membrane (Polishchuk et al, 2006). Possibly supporting this hypothesis, giardial clathrin and AP-1 were observed not only on ER-exist sites but also in PVs (Marti et al, 2003a;Marti et al, 2003b;Touz et al, 2004;Gaechter et al, 2008). As we said, the ER tubular-vesicular network apparently extends to and contacts the PVs in the periphery of the cell (Abodeely et al, 2009b) but it was recently reported that no ER membranes invade the space occupied by PVs (Faso and Hehl, 2011).…”
Section: Clathrinmentioning
confidence: 95%
See 2 more Smart Citations